The Influence of Tiktok Social Media Advertising and Brand Image on the Purchase Decision of Maybelline Products (Study on Tiktok Users in Bandar Lampung) - Kartika Chandra; Ayi Ahadiat; Mudji Rachmat Ramelan (Inovbook Publications, 2023)
The phenomenon of intense market competition has resulted in cosmetic product marketers being required to be more creative and innovative in order to compete with other local cosmetics. Companies or marketers must be able to attract consumer buying interest by utilizing social media advertising and increasing the brand image they have. The purpose of this study was to test how much influence social media advertising and brand image have on purchasing decisions for Maybelline products in Bandar Lampung. Seeing market conditions that are getting tighter, there must be a strategy to win the competition by paying attention to the use of social media which is used to advertise a product that is right and has a positive brand image that will increase the level of consumer purchases on Maybelline products. The data used in this study are primary data obtained from the results of the respondents answers collected with the help of a questionnaire. The number of samples in this study were 120 respondents. The sampling method uses purposive sampling, which is a technique for determining the sample according to the criteria determined by the researcher. The analytical method techniques used in this study were validity test, reliability test, analysis phase using multiple linear regression, and hypothesis testing, namely the t test and the coefficient of determination test (R2), with the help of the IBM SPSS 26 for windows application program. The results of this study indicate that social media advertising variables have a significant effect on purchasing decision variables.